Efektifitas Pemanfaatan Ruang Publik Melalui Taman Kota di Kabupaten Ponorogo - Yusuf Adam Hilman (Jayapangus Press, 2018)
The park’s in Ponorogo Regency, as Public Sphere, should be measured, how effective use, So it needs the studies. This research uses the method descriptive qualitative, to technique data collection of interviews and documentation. From the research the results showed, that: a park which is there are in kabupaten ponorogo a number of 6 (six), of bond issuance will be: the garden of Sukowati, a city park Singodimeja, state park Jeruk Sing, the garden of Wonopringgo, the garden of and useful for increasing the Seloaji, the garden of Pendopo, Was not effective known as of a garden, because many garden not have the concept of clear so they do not have indentitas local clear(miss identity), Lack of activity and also the spacecraft in the park made park is monotonous and less attractive, In addition there are lack of tranquility and comfort users because the park average are on main street., So that disturbed by activity motor craft. In addition the park is not in design with essentially and perfectly morally good, because there are a lot a park which is not having a place like (gazebo) or (joglo) as a barrier there awaits a mighty the rays of the sun and also the match winner the one hour heavy rain that every single time could possibly have happened. Of the existence of a park maximally while previous the if formed in the a day longer provided that with the concept of the Habermas, related to a public hal , made itself visible since its is still far away from the size of a room to lower the key how forbid that it should have a public hall no protector against god of inclusion of, the remembrance of public room which is there are in Ponorogo Regency is still in personal, because they have not been create a it cannot be built interactions among society in the Ponorogo Regency. While the concept of egalitarian societies have been fulfilled , its power because all men able to access the garden of them and they will come there is pressure to show off on doing ruts in a public hall reflected the bank sound assets.